Impact of Weight Reduction on Thyroid Function and Nonalcoholic Fatty Liver among Egyptian Adolescents with Obesity - Mona Karem Amin; Ahmed Ibrahim Ali; Hesham Elsayed (International Journal of Endocrinology)
Background. The prevalence of childhood obesity has been increasing worldwide. This may explain the emergence of nonalcoholic fatty liver as the leading cause of liver disease. Several previous studies have addressed the association between thyroid function and nonalcoholic fatty liver disease. Objectives. To study the impact of weight reduction through lifestyle modifications in adolescents with obesity. Methods. A prospective cohort study was done on 61 adolescents with obesity. Patients were evaluated at the first visit by the full history, clinical examination, and investigations (thyroid profile, lipid profile, liver function tests, HbA1c, and liver ultrasonography) as basal information. The intervention program included a dietary program, increasing physical activity, and decreasing sedentary activity. A postintervention evaluation was done at the end of six months which included anthropometric measures, laboratory results, and ultrasonographic estimation. Results. It was shown that the mean BMI of the participants had significantly decreased after lifestyle modification from (32.05 ± 3.36 kg/m2) to (28.1 ± 2.77 kg/m2) (P<0.001). It also showed that the percentage of studied adolescents with elevated TSH decreased from 47.5% to 19.7% after the weight reduction program. Improvement was also achieved in the lipid profile and liver functions. The percentage of studied adolescents with ultrasound appearance of NAFLD decreased from 31.1% to 26.2% after weight reduction. Conclusions. Lifestyle modification positively influences the metabolic derangement in obesity without medical treatment. ΔTSH is a significant predictor of the change in BMI z-score. It is also possible that hepatic steatosis affects thyroid function rather than the other way around.